Family Development Session as An Effort To Empower The Community in The Family Hope Program Gorontalo City - Setiyowati, Endah; Rahman, Misran; Luthfi Ardhian, Nur; Ibrahim, Muhammad (Universitas Negeri Padang, 2023)
Family Development Session is one of the supporting activities as well as intervention in the form of efforts to change the mindset of beneficiary families in the implementation of alleviating pre-prosperous families, namely the Family Hope Program (PKH). PKH is a social assistance program that is given conditionally. The focus of the research is to determine the efforts to empower the economic empowerment of beneficiary families through FDS activities. The research used a qualitative approach. The data collection techniques used are interviews, observation, and documentation. Checking the validity of data using triangulation techniques and sources, then the data analysis used is the domain and taxonomy of the Spradely model. The results of this study FDS as one of PKH activities were carried out in a structured manner in accordance with 5 modules and new additions, namely material on stunting prevention provided. The implementation of FDS as an empowerment effort is also supported by additional activities and other complementary empowerment programs that support the acceleration of the alleviation of underprivileged families such as the Kelompok Usaha Bersama (KUBE) and Pahlawan Ekonomi Nusantara (PENA) when the implementation of FDS is carried out. The PENA program as a form of empowerment intervention for families is considered effective because it has given birth to various forms of entrepreneurship with turnover that can deliver graduation